2013
DOI: 10.5507/bp.2011.061
|View full text |Cite
|
Sign up to set email alerts
|

The role of adrenomedullin and galanin in recurrent vasovagal syncope: a case control study

Abstract: Aims. Orthostatic stimuli are known to elicit changes in vasoactive peptide levels. The hypothesis of no difference in adrenomedullin and/or galanin levels in patients with recurrent vasovagal syncope and healthy controls was tested in a passive 35-min head-up tilt test (HUTT). Methods. Twenty eight persons (14 patients and 14 healthy controls) were tested in a 35-min/60° head-up tilt test with telemetry monitoring. Three blood samples were evaluated for each person during the HUTT. Plasma levels of adrenomedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Plasek et al [20] obtained slightly different results from the Bondanelli et al study [19]. GAL increase differentiated cases from controls better than it differentiated positive and negative responses to HUTT, i.e.…”
Section: Galaninmentioning
confidence: 83%
See 1 more Smart Citation
“…Plasek et al [20] obtained slightly different results from the Bondanelli et al study [19]. GAL increase differentiated cases from controls better than it differentiated positive and negative responses to HUTT, i.e.…”
Section: Galaninmentioning
confidence: 83%
“…In this regard, changes in circulatory catecholamines have tended to be of greatest interest given the apparent association of VVS with anxiety or stress states [8][9][10][11][12][13][14]. However, the potential role of NPs has also attracted attention; specifically, BNP [8], vasopressin (VP) [8,15,16], atrial natriuretic peptide (ANP) [8,17], adrenomedullin (ADM) [17][18][19], galanin (GAL) [19,20], and endothelin-1 (ET-1) [17,[21][22][23]. A summary of the primary physiologic effects of these NPs is shown in Table 2.…”
Section: Neuropeptides and Peptide Hormones In The Pathophysiology Ofmentioning
confidence: 99%
“…The role of ADM in VVS has been the subject of several reports but currently its impact remains unclear. Plasek et al (40) did not observe a significant difference in ADM levels in a study comparing of 14 HUT-positive patients with a cohort of 14 HUT-negative control group. Gajek et al (41) observed ADM to rise substantially in patients who developed VVS during the passive phase of HUT (but not if nitroglycerin-induced) On the other hand, Hamrefors et al (42) observed that in patients >40 years of age, lower supine MR-pro-ADM predicted asystolic VVS on HUT, although orthostatic levels of the biomarker were not assessed.…”
Section: Adrenomedullinmentioning
confidence: 87%
“…Plasek et al (40) obtained slightly different results. These authors observed an increase in plasma galanin for VVS patients during HUT, regardless of whether they developed syncope or not during the test.…”
Section: Galaninmentioning
confidence: 94%